Metode Follow The Line dalam Pembelajaran Menulis Huruf Arab pada Anak Usia Dini - Irman Sumantri (Kiddo: Jurnal Pendidikan Islam Anak Usia Dini, 2022)
This study aims to find the conditions for implementing the follow the line method in learning to write Arabic letters in Haura early childhood education, Cigudeg district, Bogor district. Quantitative descriptive research method with observation data instruments and questionnaires. The results of the study show that 1) the teacher has not implemented the method of following the line on his students on a regular basis, causing many of his students to be less proficient in writing Arabic letters; 2) there are several obstacles faced by teachers in implementing the method of following the flow both internally and externally. This study recommends to further researchers to design new, varied learning that can foster children's interest and motivation in learning to achieve the school's vision and national education goals.